Perlawanan Visual Perempuan dalam Poster - Misbah Zulfa Elizabeth (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2017)
Visual expression is something un-denayable in social life because the viasuality is the expression of the social life. This article has the purpose to explore how visual expression of women resistance toward gender inequality. Applying qualitative research with the method of documentation study this article in detail analyses the interpretation of religious text as the source of inequality and gender reality in social context. It is revealed that visual expression of the poster suggesting to treat men and women respectfully is the resistance toward religious text interpretation which is inequally treat men and women.